Background rates of disease in Latin American children from a rotavirus vaccine study. Issue 8 (3rd August 2017) - Baay, Marc; Bollaerts, Kaatje; Struchiner, Claudio; Verstraeten, Thomas
ABSTRACT: Background: Knowledge of background rates of adverse events is crucial to assess vaccine safety concerns. We used data from a rotavirus vaccine study (Ruiz-Palacios et al., NEJM, 2006) including 63, 225 infants from 11 Latin American countries to investigate reporting rates of serious adverse events (SAEs) among these infants, and describe rates by country, gender, age, and season. Methods: For this randomized, double-blind, placebo-controlled, phase 3 trial, investigators from Argentina, Brazil, Chile, Colombia, Dominican Republic, Honduras, Mexico, Nicaragua, Panama, Peru, and Venezuela recruited 6-to-13-week-old healthy infants. The infants received 2 oral doses of vaccine or placebo. The study population was followed 100 d for the assessment of adverse events. SAEs were captured by an active surveillance system. Results: Strong differences in event rates could be observed between countries (min. 48.1/10, 000 person-years in Dominican Republic/Peru; max. 296.2/10, 000 person-years in Brazil) and between genders: gastroenteritis, pneumonia, bronchiolitis and bronchitis occurred significantly more frequently in males. In addition, infections and infestations, and most disorders, including immune system and cardiac disorders, were more frequent at earlier ages. Finally, looking at seasonality we noted higher rates of SAEs in the second half of the year in all countries except Mexico. Discussion: Significant differences in reporting rates of SAEs between countries, gender and calendar months illustrate the importance of knowing the local epidemiology when interpreting SAEs. Data from clinical trials can be used to better understand background rates of diseases that may be perceived as potential adverse events following immunization.